Crystal structure of the possible sulindac impurity 2-(5-fluoro-2-methyl-1H-inden-3-yl)acetonitrile - Wu Yun-Deng; Wan Hui; Xia Yun; Ni Jie; Li Jian; Zhang Hui; Xu Xiang-Yang; Xie Jun (Acta Crystallographica Section E: Crystallographic Communications)
The title compound,C12H10FN, was identified as a possible critical degradation impurity of sulindac, a therapeutic COX-2 inhibitor for rheumatoid arthritis. Single-crystal X-ray analysis revealed two conformationally slightly different molecules in the asymmetric unit (Z′ = 2), each containing an indene ring system. In the crystal structure, [100] chains formed through C—H...N interactions are connected into a tri-periodic supramolecular structure by further C—H...F and C—H...π interactions through P21/n symmetry operations.